2022
DOI: 10.1080/26410397.2022.2068211
|View full text |Cite
|
Sign up to set email alerts
|

“Our mothers do not tell us”: a qualitative study of adolescent girls’ perspectives on sexual and reproductive health in rural Nepal

Abstract: Adolescent girls in low- and middle-income countries continue to face poor sexual and reproductive health (SRH). In Nepal, early marriage and motherhood, gender-based violence, and unmet need for contraception remain pervasive. Adolescent girls in rural areas bear a disproportionate burden of poor reproductive health outcomes, but there are limited context-specific data. This is a qualitative study to identify factors that impact adolescent girls’ utilisation of and access to SRH services in a rural district o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…More than half adolescents had never communicated on SRH topics with their parents [ 12 ]. In addition, similar to the previous studies [ 9 , 12 , 13 , 15 ], most parents in this study perceived difficulty in explaining SRH issues. Social stigma or fear of social disapproval and feelings of lack of sexual health information were seen as barriers to limited parental-adolescent communication on sexual health matters.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…More than half adolescents had never communicated on SRH topics with their parents [ 12 ]. In addition, similar to the previous studies [ 9 , 12 , 13 , 15 ], most parents in this study perceived difficulty in explaining SRH issues. Social stigma or fear of social disapproval and feelings of lack of sexual health information were seen as barriers to limited parental-adolescent communication on sexual health matters.…”
Section: Discussionsupporting
confidence: 86%
“…context, including the practice of parental and adolescent communication about sexual health issues [12,13]. This study showed that parents from Brahmin/Chhetri ethnic group were more likely to communicate about sexual health matters with their adolescent children compared to the Newar ethnic group.…”
Section: Plos Onementioning
confidence: 77%
See 3 more Smart Citations